Arbuscular mycorrhizae in sand dune plants of the north atlantic coast of the U.S.: Field and greenhouse inoculation and presence of mycorrhizae in planting stock - Gemma, J. N.; Koske, R. E. (Journal of Environmental Management, 1997)
The ability of several sand dune inhabiting plant species to successfully colonize dune sites appears to depend upon the presence in the soil of arbuscular mycorrhizal fungi (AMF) that form mutualistic associations with roots. Dune sites barren of vegetation lack these fungi whose large spores are not readily dispersed to the root zones. Despite the absence of these beneficial fungi from barren sites, however, plantings made in AMF-free dune soils eventually form the mycorrhizal association. Examination of planting stock of several species of plants that are used to vegetate barren sand dunes and dune flats of the eastern seaboard of the U.S.A. revealed that AMF were routinely present in the planting materials prior to outplanting. AMF occurred in planting stock of seven varieties of Ammophila breviligulata, and in Prunus maritima, Rosa rugosa, and Spartina patens, but were absent from Myrica pensylvanica. In a field planting in a previously barren deflation zone in the large parabolic dunes of Cape Cod National Seashore, Massachusetts, culms of A. breviligulata that were inoculated with native species of AMF produced more tillers and inflorescences than did non-inoculated plants, even though 78% of the latter had become mycorrhizal 47 weeks after planting. In greenhouse experiments, P. maritima was found to have an absolute requirement for AMF and Solidago sempervirens was not. The significance of the presence of AMF in planting stock for revegetation and restoration of previously unvegetated sites lacking in AMF is discussed.